Exposure to particles and fungi in Portuguese swine production - Viegas, Susana (2013)
A number of studies have shown that exposure to airborne dust and microorganisms can cause respiratory diseases in humans. Agricultural workers, such as pig farmers, have been found to be at high risk of exposure to airborne particles. The aim of this study was to detect contamination caused by particles and fungi in 7 swine farms located in Lisbon district, Portugal. Environment evaluations were performed during the winter season of 2011 with a portable direct-reading equipment (Lighthouse, model 3016 IAQ) and it was possible to obtain data concerning contamination caused by particles with 5 different sizes (PM0.5; PM1; PM2.5; PM5; PM10). To assess air contamination caused by fungi, air samples of 50 liters were collected us-ing a Millipore Air Tester (Millipore) by impaction method at a velocity of 140 L / minute and at one meter height, using malt extract agar supplemented with chloramphenicol (0.5%). Air sampling was also performed outside premises, since this is the place regarded as reference. All the collected samples were incubated at 27 ºC for 5 to 7 days. Results from particles’ contamination showed that higher values were connected with PM5 and PM10 sizes and that smaller particles exhibit lower contamination values. Concerning the fungal load of the analyzed swine, the highest obtained value was 4100 CFU/m3 and the lowest was 120 CFU/m3. Forty six different fungal species were detected in the air, being Aspergillus versicolor the most frequent species found (20.9%), followed by Scopulariopsis brevicaulis (17.0%) and Penicillium sp. (14.1%). Data gathered from this study corroborate the need of monitoring the contamination by particulate matter, fungi and their metabo-lites in Portuguese swine.